Primary lumbar hydatid cyst: a case report - Arslan, Serkan; Turan, Cüneyt; Sezer, Saadettin; Tuna, Ibrahim Sacit (The Turkish Journal of Pediatrics, 2010)
A five-year-old male patient presented with swelling in the lumbar region that had persisted for two weeks. Ultrasonography and magnetic resonance imaging revealed a cystic lesion inside his right back muscles. Intra-abdominal organs within the site of inspection were normal. The lumbar region was explored, and a 3x4x5 cm hydatid cyst was detected inside the latissimus dorsi muscles. The cyst was incised and the germinative membrane was removed. Albendazole was used for three months after surgery to prevent recurrences. No problem was detected in a five-year follow-up period. Primary hydatid cyst in the lumbar area is very rare. In hydatid cyst treatment, it is necessary to remove the cyst without contaminating adjacent organs. Medical treatment as an adjunct to surgery increases the chance of full recovery.